Peran Mediasi Struktur Modal Pada Pengaruh Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan Sektor Non-Cyclical - Meirisa, Faradila (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2025)
This research aims to prove whether capital structure can mediate the relationship between profitability and liquidity on company value. The types of research used are descriptive and associative research. In determining investment decisions, investors need to consider the company value which describes the welfare provided by the company. The analysis technique used is PLS-SEM (Partial Least Square) with a research sample of 75 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) in 2020-2023. The results of this research show that. Profitability has a positive and significant effect on capital structure, liquidity has no effect on capital structure, capital structure has a positive and significant effect on company value, profitability has a negative and significant effect on company value, liquidity has a positive and significant effect on company value and capital structure can mediate the effect of profitability and liquidity on company value.